2015
DOI: 10.1016/j.biomaterials.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Improved intervention of atherosclerosis and cardiac hypertrophy through biodegradable polymer-encapsulated delivery of glycosphingolipid inhibitor

Abstract: D-Threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), a glycosphingolipid synthesis inhibitor, holds promise for the treatment of atherosclerosis and cardiac hypertrophy but rapid in vivo clearance has severely hindered translation to the clinic. To overcome this impediment, we used a materials-based delivery strategy wherein D-PDMP was encapsulated within a biodegradable polymer composed of poly ethylene glycol (PEG) and sebacic acid (SA). PEG-SA was formulated into nanoparticles that were doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…The nearly normal serum TG levels in all groups could probably explain why all treatments had no effects on TG metabolism. Besides, the medication time may partly explain the different effects on LDL-C levels, as according to their reported data, 24-or 16-weeks d-PDMP treatment approximately reduced serum LDL-C levels by 70% or 30% [10,23]. But above all, the data do suggest that d-PDMP could inhibit atherosclerosis, although serum cholesterols were not reduced below some certain threshold.…”
Section: Gonadal Fat-pad Mass In Myriocin-treated Apoe −/− Mice Was Smentioning
confidence: 94%
“…The nearly normal serum TG levels in all groups could probably explain why all treatments had no effects on TG metabolism. Besides, the medication time may partly explain the different effects on LDL-C levels, as according to their reported data, 24-or 16-weeks d-PDMP treatment approximately reduced serum LDL-C levels by 70% or 30% [10,23]. But above all, the data do suggest that d-PDMP could inhibit atherosclerosis, although serum cholesterols were not reduced below some certain threshold.…”
Section: Gonadal Fat-pad Mass In Myriocin-treated Apoe −/− Mice Was Smentioning
confidence: 94%
“…PDMP, a ceramide analogue, is a promising target for preventing cardiovascular diseases such as atherosclerosis and cardiac hypertrophy 30,31 and for suppressing osteoclastogenesis by inhibiting glycosphingolipid synthesis. 31,32 Ode et al 33 findings demonstrated that PDMP reduced osteoblastic proliferation and pre-osteoblastic cell differentiation by translocation of mTORC1 from late endosome/lysosome (LE/Ly) to the endoplasmic reticulum (ER), suggesting inhibition of mTORC1 activity. This inhibitory action of ceramide analogue allows normal lysosomal functioning or lysosomal activation and their fusion with MVBs.…”
Section: Introductionmentioning
confidence: 99%
“…Previously we found that the encapsulation of D-PDMP within a biopolymer, consisting of polyethylene glycol and sebacic acid, increased gastrointestinal absorption of D-PDMP, and increased its longevity in ApoE−/− mice from less than 1 hr, for the unconjugated D-PDMP, to ~48 hours 52 62 . Consequently, 1 mpk of BPD was equally efficacious as 10 mpk of free D-PDMP in decreasing LacCer levels in aortic tissue in ApoE−/− mice 37 .…”
Section: Discussionmentioning
confidence: 97%